Flexural failure of the unrestrained segment for sleeved compression struts with pinned ends. (March 2023) - Shi, Hai-Rong; Chen, Ying; Wang, Chun-Lin; Zeng, Bin
Abstract: Confining with an outer sleeve is an effective means of enhancing the load-bearing and deformation capacity of compression struts. The outer sleeve and compression strut, i.e., inner core, constitute a sleeved core-loaded member, where the latter ideally bears all the axial compression under the lateral restraint of the former. Additionally, an extension segment of the inner core is typically required as the allowance for contraction. However, the unrestrained extension segment is prone to excess flexural deformation, dramatically decreasing the overall load carrying capacity of the sleeved member. In this paper, first, an analytical investigation of the behaviour of the sleeved member with pinned ends is presented. Second, a numerical study was conducted to determine the limit state of the localized flexural failure and to propose the corresponding design criterion combining the analytical model. Last, the design criterion was further validated by compressive tests, indicating that the proposed method accurately predicted the localized​ flexural failure of both seamless-sleeved members and members with assembled outer sleeves. Highlights: A theoretical model on the localized flexural failure of sleeved members is built up. The corresponding design criterion is proposed combining numerical cases. The unrestrained length ratio of the core and the gap width exhibit notable effects. The theory is validated by tests on both seamless- and assembled-sleeved members.